Conductive material, negative plate, battery, battery pack and electric equipment
By using the conductive material of the inorganic oxide shell on the surface of the battery negative electrode sheet, the problems of poor liquid absorption and liquid retention capacity of the battery and large internal resistance are solved, and a higher first-time Coulomb efficiency and cycle life are achieved.
Patent Information
- Application Number
- CN202411531938.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-04-08
AI Technical Summary
The existing batteries have defects such as poor liquid retention ability of the battery to absorb and retain liquid on the electrolyte, large internal resistance of the battery (especially large internal resistance under low temperature conditions), first-time Coulomb efficiency and poor cycle life.
It is provided with a conductive material, including a conductive agent and an inorganic oxide shell present on the surface of the conductive agent. The oil absorption value of the conductive material is 100 mL/100g-350 mL/100g. It is applied to the negative electrode sheet of the battery to form a continuous conductive network, reduce internal resistance, and improve liquid retention ability and battery performance.
This conductive material improves the battery's liquid absorption and retention ability, reduces the DC internal resistance under low temperature conditions, and improves the first Coulomb efficiency and cycle life.
Smart Images

Figure BDA0005111294420000151
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a conductive material, a negative electrode sheet, a battery, a battery pack and an electrical device. Background Art
[0002] Batteries are common electrochemical devices with a wide range of applications. For example, lithium-ion batteries, as a lightweight, efficient, and long-life energy storage device, are an indispensable core component of power-consuming devices such as mobile electronic devices, electric vehicles, and even renewable energy systems. However, existing batteries generally have defects such as poor electrolyte absorption and retention, large internal resistance (especially high internal resistance under low temperature conditions), first coulomb efficiency (first efficiency), and poor cycle life, which need to be solved urgently. Summary of the invention
[0003] The main purpose of the present invention is to provide a conductive material, which can be applied to the negative electrode sheet of a battery to improve the battery's liquid absorption and retention capacity, reduce the battery's low-temperature DC internal resistance, and improve the battery's initial coulombic efficiency and cycle life.
[0004] The present invention also provides a negative electrode sheet, which includes the above-mentioned conductive material and is applied to a battery to improve the battery's liquid absorption and retention capacity, reduce the battery's low-temperature DC internal resistance, and simultaneously improve the battery's first coulomb efficiency and cycle life and other performance.
[0005] The present invention also provides a battery, comprising the above-mentioned negative electrode sheet, so that the battery has excellent liquid retention capacity, lower low-temperature direct current internal resistance, and excellent first coulomb efficiency and cycle performance.
[0006] The present invention also provides a battery pack, comprising the above-mentioned battery, so that the battery pack has excellent liquid retention capacity, lower low-temperature DC internal resistance, and excellent first coulomb efficiency and cycle performance.
[0007] The present invention also provides an electrical device, comprising the above-mentioned battery or battery pack, so that the performance of the battery related to the electrical device is relatively excellent.
[0008] In a first aspect, the present invention provides a conductive material, comprising a conductive agent and a shell layer present on the surface of the conductive agent, wherein the shell layer comprises an inorganic oxide;
[0009] The oil absorption value of the conductive material is 100 mL / 100 g to 350 mL / 100 g.
[0010] The conductive material as described above has an oil absorption value of 260 mL / 100 g to 350 mL / 100 g.
[0011] The conductive material as described above has a specific surface area of 20 m2 / g-200m 2 / g, preferably 50m 2 / g-80m 2 / g.
[0012] For the conductive material as described above, the thickness of the shell layer is 2nm-20nm, preferably 3-6nm.
[0013] The conductive material as described above, wherein the inorganic oxide comprises at least one of aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, manganese oxide, and zinc oxide;
[0014] And / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene.
[0015] In a second aspect, the present invention provides a negative electrode sheet, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the conductive material as described above.
[0016] The negative electrode sheet as described above, wherein the conductive material accounts for 0.01%-2% by mass of the negative electrode active material layer;
[0017] And / or, the negative electrode active material layer also includes a negative electrode active material, a thickener, and a binder, the mass percentage of the negative electrode active material in the negative electrode active material layer is 80%-98%, the mass percentage of the thickener in the negative electrode active material layer is 0.5%-5%, and the mass percentage of the binder in the negative electrode active material layer is 0.5%-5%.
[0018] In a third aspect, the present invention provides a battery comprising the negative electrode sheet as described above.
[0019] In a fourth aspect, the present invention provides a battery pack comprising the battery as described above.
[0020] In a fifth aspect, the present invention provides an electrical device comprising the battery as described above or the battery pack as described above.
[0021] The conductive material provided by the present invention comprises a conductive agent and a shell layer present on the surface of the conductive agent, wherein the shell layer is an inorganic oxide, and the oil absorption value of the conductive material is 100mL / 100g-350mL / 100g. The conductive material is applied to the negative electrode sheet of the battery to improve the liquid absorption and retention capacity of the battery, reduce the low-temperature DC internal resistance of the battery, and take into account the improvement of the first coulomb efficiency and cycle life of the battery. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the related technologies, existing batteries generally have defects such as poor electrolyte retention and absorption capacity of the battery cells, large internal resistance of the battery (especially the internal resistance under low temperature conditions), first coulomb efficiency (first efficiency) and poor cycle life, which need to be solved urgently.
[0024] With the continuous evolution of technology and the growing market demand, higher and higher requirements are placed on the battery's kinetic performance and cycle life. Among them, conductive agents, as an important component of battery electrode materials, play an indispensable role in improving the overall performance of batteries. Specifically, in lithium-ion batteries, the main function of conductive agents is to improve the conductivity of the electrodes and ensure that the battery has good electrochemical properties during the charging and discharging process.
[0025] According to the research of the inventors of this application, although the cycle performance of the battery can be improved to a certain extent by adjusting structural parameters such as the size and shape of the conductive agent in the negative electrode sheet, adjusting the amount of conductive agent added in the negative electrode sheet, and introducing ion conductive agents into the negative electrode sheet, these control measures are still difficult to take into account improving the battery's ability to absorb and retain liquid, reducing the battery's internal resistance (especially the internal resistance under low temperature conditions), and improving the battery's first coulombic efficiency and cycle life.
[0026] For example, if the amount of conductive agent added to the negative electrode sheet is increased, complex side reactions will occur at the conductive agent-electrolyte interface, excessive consumption of active lithium and electrolyte, resulting in battery capacity decay and a significant decrease in coulombic efficiency; and if the amount of conductive agent added to the negative electrode sheet is reduced, it will easily cause the graphite to shrink and form graphite islands during the charge and discharge cycle of the battery, thereby reducing the battery cycle performance and other electrical properties.
[0027] For example, by adjusting the structural parameters such as the size and shape of the conductive agent in the negative electrode sheet, such as using a zero-dimensional conductive agent or a two-dimensional conductive agent (linear conductive agent), due to the low mechanical strength of carbon black, the shrinkage and expansion of graphite during use can easily lead to reduced contact between graphites, or even material falling off, thereby causing performance degradation. When using linear conductive agents, such as carbon tubes, due to their high specific surface area, serious conductive agent-electrolyte side reactions will occur, further consuming active lithium and electrolyte, resulting in a significant decrease in battery capacity and coulombic efficiency.
[0028] For example, if an ion conductor is introduced into the negative electrode sheet, due to the poor conductivity of the ion conductor itself, the excessive introduction of the ion conductor will easily cause the graphite to shrink during the charge and discharge cycle of the battery to form islands and internal short circuits, thereby reducing the battery's cycle performance, while adding a small amount of ion conductor will reduce the battery's first coulombic efficiency.
[0029] Based on this, in the first aspect, the present invention provides a conductive material, comprising a conductive agent and a shell layer present on the surface of the conductive agent, the shell layer comprising an inorganic oxide; the oil absorption value of the conductive material is 100mL / 100g-350mL / 100g, for example, it can be 100mL / 100g, 120mL / 100g, 140mL / 100g, 160mL / 100g, 200mL / 100g, 250mL / 100g, 300mL / 100g, 350mL / 100g or a range composed of any two of them.
[0030] The conductive material of the present invention is applied to the negative electrode sheet of the battery, which can improve the liquid absorption and retention capacity of the battery, reduce the low-temperature DC internal resistance of the battery, and improve the first coulomb efficiency and cycle life of the battery.
[0031] The conductive material in the present invention is coated with a shell on the surface of the conductive agent, and the shell includes an inorganic oxide. The inorganic oxide shell has excellent electrical conductivity and stability, and can maintain good electronic conductivity under low temperature conditions. The presence of the shell can form a continuous conductive network, reduce the contact resistance between the conductive agent particles, and thus reduce the DC internal resistance of the battery. Inorganic oxides have good lyophilicity, which can enhance the adsorption and retention capacity of the conductive material to the electrolyte. The presence of the shell can increase the surface activity of the conductive agent and improve its liquid retention capacity. The good chemical stability of the inorganic oxide shell can reduce the occurrence of side reactions during the first charge and discharge process and reduce irreversible capacity loss. This can improve the first coulomb efficiency of the battery. In addition, the inorganic oxide shell can protect the conductive agent and electrode materials during the charge and discharge cycle, reducing structural changes and performance attenuation. The presence of the shell can improve the structural stability of the electrode material and extend the cycle life of the battery. Due to the low dielectric constant of the inorganic oxide material, excessive consumption of the electrolyte caused by the growth of the SEI film on the surface of the conductive material can be avoided, thereby improving the first coulomb efficiency and cycle stability of the battery.
[0032] At the same time, the oil absorption value of the conductive material is in the range of 100mL / 100g-350mL / 100g, indicating that the conductive material has an appropriate pore structure, which is conducive to the penetration and distribution of the electrolyte, improves the overall conductivity of the conductive material, and can effectively reduce the DC internal resistance of the battery, especially under low temperature conditions. And the good pore structure of the conductive material can effectively adsorb and retain the electrolyte, ensure the uniform distribution of the electrolyte in the electrode material, thereby improving the battery's liquid retention capacity. It enables the electrode material to fully react during the first charge and discharge process, improves the charge utilization rate, and thus improves the first coulomb efficiency. In addition, the uniform distribution and retention of the electrolyte can reduce the expansion and contraction of the electrode material during the cycle, maintain the structural integrity of the electrode material, and thus improve the cycle performance of the battery.
[0033] Therefore, the conductive material provided by the present invention includes a conductive agent and a shell layer present on the surface of the conductive agent, and the shell layer is an inorganic oxide. The oil absorption value of the conductive material is 100mL / 100g-350mL / 100g. The conductive material is applied to the negative electrode sheet of the battery to improve the liquid absorption and retention capacity of the battery, reduce the low-temperature DC internal resistance of the battery, and take into account the improvement of the battery's first coulomb efficiency and cycle life and other performance.
[0034] The present invention does not limit the preparation method of the conductive material, and a coating layer can be formed on the surface of the conductive agent by conventional methods in the art. For example, the preparation method can be at least one of an acid-base two-step method, a microemulsion method, an emulsion gel method, a hydrolysis method, a precipitation method, and a hydrothermal method.
[0035] Specifically, the conductive material of the present invention can be prepared by atomic deposition method, which may include the following steps:
[0036] After placing the conductive agent in a stainless steel mesh mold, the whole is placed in an atomic layer deposition chamber, evacuated, and the temperature of the chamber is maintained at about 200°C-250°C. Inorganic oxide source vapor and water vapor at room temperature are introduced into the chamber, and then the chamber is evacuated and allowed to stand, and inorganic oxide source vapor is introduced again after a certain period of time to complete a cycle of deposition. This step is repeated 10 to 40 times to obtain an inorganic oxide-coated conductive material.
[0037] In some embodiments, the conductive agent may include at least one of conductive carbon black, carbon nanotubes, and graphene, preferably conductive carbon black.
[0038] The present invention can use at least one of conventional conductive carbon black, carbon nanotubes, and graphene in the art, which can be commercially available or prepared by conventional methods in the art. For example, the conductive carbon black can include at least one of acetylene black, furnace black, channel black, thermal black, lamp black, and Ketjen black, preferably furnace black.
[0039] In some embodiments, the inorganic oxide includes inorganic metal oxides and inorganic transition metal oxides. Specifically, the inorganic oxide includes at least one of aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, manganese oxide, and zinc oxide, preferably at least one of aluminum oxide, titanium oxide, and silicon oxide, and more preferably aluminum oxide.
[0040] Because the above inorganic oxides have excellent chemical stability, they can effectively protect the conductive agent from chemical corrosion in the environment. In addition, the above inorganic oxides can enhance the mechanical strength and wear resistance of the conductive material, provide additional structural support, and reduce the damage of the conductive material under mechanical stress. The conductive material is applied to the negative electrode of the battery, which can further improve the battery's ability to absorb and retain liquid, reduce the battery's low-temperature DC internal resistance, and improve the battery's first coulomb efficiency and cycle life.
[0041] In some embodiments of the present invention, the oil absorption value of the conductive material is 260mL / 100g-350mL / 100g, for example, it can be 260mL / 100g, 270mL / 100g, 280mL / 100g, 290mL / 100g, 300mL / 100g, 310mL / 100g, 320mL / 100g, 330mL / 100g, 340mL / 100g, 350mL / 100g or a range composed of any two of them.
[0042] As a preferred solution for the oil absorption value of the conductive material, the oil absorption value is 260mL / 100g-350mL / 100g, indicating that the conductive material has a higher porosity. This structure helps to form a more continuous and uniform conductive network, reducing the contact resistance between the conductive agent particles, thereby reducing the DC internal resistance of the battery, especially under low temperature conditions. A higher oil absorption value means that the conductive material can better adsorb and retain the electrolyte, ensuring the uniform distribution of the electrolyte inside the conductive agent and in the electrode material. This helps to improve the conduction efficiency of electrons and ions and further reduce the DC internal resistance at low temperatures.
[0043] In addition, the oil absorption value is 260mL / 100g-350mL / 100g, and the conductive material has excellent electrolyte adsorption and retention capabilities. A higher oil absorption value means that the conductive material can absorb more electrolyte, ensuring the uniform distribution and stable existence of the electrolyte in the electrode material, thereby improving the battery's electrolyte retention capacity. It can also reduce the loss of electrolyte during the battery's charge and discharge cycle, reduce the performance degradation of the electrode material during the cycle, and increase the battery's cycle life.
[0044] In addition, the higher oil absorption value ensures that the conductive material can fully adsorb and retain the electrolyte during the first charge and discharge process, reducing side reactions on the surface of the electrode material and reducing irreversible capacity loss, thereby improving the first coulombic efficiency of the battery.
[0045] In some embodiments of the present invention, the specific surface area of the conductive material is 20 m 2 / g-200m 2 / g, for example, it can be 20m 2 / g, 30m 2 / g, 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g or any two of them. Preferably 50m 2 / g-80m 2 / g.
[0046] The specific surface area of the conductive material in the present invention is within the above range, which can provide more contact points and paths, form a more continuous conductive network, help improve the efficiency of electronic conduction, and reduce the internal resistance of the battery. It also helps to evenly distribute the current, reduce local hot spots and current density concentration, and thus improve the overall conductivity and stability of the battery.
[0047] In addition, the conductive material has more pores and surface, which can absorb and retain more electrolyte. This helps to ensure the uniform distribution of electrolyte in the electrode material and improve the battery's ability to retain electrolyte. It reduces the loss of electrolyte during the battery's charge and discharge cycle, maintains the activity of the electrode material, and improves the overall performance of the battery.
[0048] In addition, conductive materials with appropriate specific surface area can distribute electrolyte more evenly, reduce side reactions on the surface of electrode materials, reduce irreversible capacity loss, and thus improve the first coulombic efficiency. Ensuring the uniform distribution of electrolyte in electrode materials allows electrode materials to fully react during the first charge and discharge process, improves charge utilization, and thus improves the first coulombic efficiency.
[0049] In addition, conductive materials with appropriate specific surface area can absorb and retain more electrolyte, reduce the expansion and contraction of electrode materials during the charge and discharge cycle, maintain the structural integrity of electrode materials, and thus improve the cycle performance of the battery. Ensure the uniform distribution and stable existence of electrolyte in the electrode material, reduce the performance degradation of electrode materials during the cycle, and improve the cycle life of the battery.
[0050] In some embodiments of the present invention, the thickness of the shell layer is 2 nm-20 nm, for example, 2 nm, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm or any two thereof, preferably 3 nm-6 nm.
[0051] The shell thickness of the conductive material in the present invention is within the above range, which can form a continuous and uniform conductive network to ensure effective conduction of electrons between the conductive agent particles. Too thick a shell may increase the resistance of the electron conduction path, while too thin a shell may not form an effective conductive network. A moderate shell thickness helps to reduce the direct current internal resistance (DCIR) of the battery and improve the power output capacity and charge and discharge efficiency of the battery.
[0052] On the other hand, the thickness of the shell layer of the conductive material is within the above range, which can ensure that the surface of the conductive material has an appropriate pore structure, which is conducive to the penetration and retention of the electrolyte. A too thick shell layer may hinder the penetration of the electrolyte, while a too thin shell layer may not provide sufficient liquid retention capacity. A moderate shell layer thickness ensures the uniform distribution of the electrolyte in the conductive material, reduces the loss of electrolyte, and enhances the battery's liquid retention capacity.
[0053] In addition, the shell thickness within the above range can effectively cover the surface of the conductive agent, reduce direct contact with the electrolyte, reduce the incidence of side reactions, thereby reducing irreversible capacity loss and improving the initial coulombic efficiency. The moderate shell thickness ensures that the surface of the conductive material has a uniform reaction interface, so that the electrode material can fully react during the initial charge and discharge process, thereby improving the charge utilization rate.
[0054] In addition, the shell thickness within the above range can provide effective protection for the conductive material during the charge and discharge cycle, reducing the structural changes and performance degradation of the conductive agent and the electrode material. A too thick shell may increase the brittleness of the material, while a too thin shell may not provide sufficient protection. A moderate shell thickness can reduce the expansion and contraction of the electrode material during the charge and discharge cycle, maintain the structural integrity of the electrode material, and thus improve the cycle life of the battery.
[0055] In some embodiments of the present invention, the conductive agent is secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 5nm-200nm, for example, it can be 5nm, 10nm, 15nm, 20nm, 50nm, 100nm, 150nm, 200nm or a range consisting of any two of them.
[0056] The primary particles in the present invention may be in a grape bunch structure, and the average particle size of the primary particles is within the above range, which can provide a higher specific surface area, help form a more continuous and uniform conductive network, improve the electron conduction efficiency, and reduce the internal resistance of the battery. Primary particles with a suitable average particle size can be more evenly distributed in the secondary particles, reducing the resistance in the electron conduction path, thereby improving the power output and charge and discharge efficiency of the battery.
[0057] In addition, the primary particles have an appropriate average particle size range, which helps to form secondary particles with an appropriate pore structure. This pore structure helps the penetration and retention of electrolytes and improves the electrolyte retention capacity of conductive materials. Primary particles with an appropriate average particle size can provide more pores and surfaces, allowing the electrolyte to be evenly distributed in the conductive material, reducing electrolyte loss and enhancing the battery's electrolyte retention capacity.
[0058] In addition, the average particle size of primary particles is in the range of 5nm-200nm, which can provide a more uniform surface and interface, reduce direct contact with the electrolyte, reduce the incidence of side reactions, thereby reducing irreversible capacity loss and improving the first coulombic efficiency. Primary particles with a suitable average particle size can provide more active sites, allowing the electrode material to fully react during the first charge and discharge process, improve charge utilization, and thus improve the first coulombic efficiency.
[0059] In addition, the primary particles have an appropriate average particle size range, which helps to form structurally stable secondary particles and reduce structural changes and performance degradation during the charge and discharge cycle. Primary particles with an appropriate average particle size can be more evenly distributed in the secondary particles, reduce expansion and contraction, maintain the structural integrity of the electrode material, and thus improve the cycle life of the battery.
[0060] In a second aspect, the present invention provides a negative electrode sheet, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the conductive material as described above.
[0061] The negative electrode sheet in the present invention includes a negative electrode active material layer, and the negative electrode active material layer includes the conductive material as described above. Therefore, the negative electrode sheet is applied to a battery to improve the battery's liquid absorption and retention capacity, reduce the battery's low-temperature DC internal resistance, and improve the battery's initial coulombic efficiency and cycle life.
[0062] In some embodiments of the present invention, the mass percentage of the conductive material in the negative electrode active material layer is 0.01%-2%.
[0063] In some embodiments, the negative electrode active material layer also includes a negative electrode active material, a thickener, and a binder. The negative electrode active material accounts for 80%-98% of the mass percentage of the negative electrode active material layer, the thickener accounts for 0.5%-5% of the mass percentage of the negative electrode active material layer, and the binder accounts for 0.5%-5% of the mass percentage of the negative electrode active material layer.
[0064] Exemplarily, the mass percentage of the conductive material in the negative electrode active material layer may be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two thereof. The mass percentage of the negative electrode active material in the negative electrode active material layer may be 80%, 85%, 90%, 92%, 95%, 98% or a range consisting of any two thereof. The mass percentage of the thickener in the negative electrode active material layer may be 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two thereof. The mass percentage of the binder in the negative electrode active material layer may be 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two thereof.
[0065] The present invention does not particularly limit the specific type of the negative electrode active material, and conventional materials in the art can be selected. For example, the negative electrode active material can be selected from at least one of graphite materials, silicon-based materials, tin-based materials, and lithium titanate materials. Among them, the graphite material can be at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres, and carbon fibers. The silicon-based material can be at least one of elemental silicon, silicon oxide, silicon alloy, and composite silicon. The tin-based material can be at least one of tin oxide and tin alloy.
[0066] The present invention does not particularly limit the specific types of thickeners and adhesives. The thickeners, adhesives and other components can be selected from conventional substances in the art. For example, the thickener can be selected from at least one of carboxymethyl cellulose sodium (CMC-Na), carboxymethyl cellulose lithium (CMC-Li), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), and natural rubber (NR). The adhesive can be selected from at least one of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber (SBR), and styrene-acrylic rubber.
[0067] The negative electrode sheet of the present invention further comprises a negative electrode current collector, and the negative electrode active material layer can be arranged on one surface or both surfaces of the negative electrode current collector.
[0068] The present invention does not limit the type of the negative electrode current collector. Preferably, the negative electrode current collector used is copper foil, and more preferably, the negative electrode current collector used is carbon-coated copper foil.
[0069] The present invention can coat the negative electrode sheet with multiple layers of negative electrode active material, add the above conductive material to one or more layers, adjust the pore structure of the negative electrode sheet, and further improve the ion transmission performance.
[0070] In a third aspect, the present invention provides a battery, comprising the negative electrode sheet as described above. The battery has the advantages corresponding to the negative electrode sheet as described above, which will not be described in detail.
[0071] The battery of the present application includes a separator, a positive electrode and an electrolyte in addition to a negative electrode sheet. The composition of the positive electrode sheet can refer to conventional positive electrode sheets in the art, and the separator can also adopt separators conventionally used in the art, such as PP film, PE film, PVDF film, etc. The electrolyte is not limited and can be selected according to actual conditions.
[0072] The battery includes but is not limited to a lithium-ion battery and a sodium-ion battery. When the battery is a lithium-ion battery, the positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphate containing an olivine structure; when the battery is a sodium-ion battery, the positive electrode active material may include at least one of a transition metal oxide, a polyanionic compound, an organic polymer, and a Prussian blue material.
[0073] The battery of the present application can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and the battery cell can be obtained through a stacking or winding process, and then through baking, liquid injection, formation, packaging and other processes to obtain the above-mentioned battery.
[0074] In a fourth aspect, the present invention provides a battery pack, comprising the battery as described above. The battery pack has the advantages corresponding to the above-mentioned negative electrode sheet, which will not be described in detail.
[0075] In a fifth aspect, the present invention provides an electrical device, comprising the battery as described above or the battery pack as described above. The electrical device has the advantages corresponding to the above-mentioned negative electrode sheet, which will not be described in detail.
[0076] The electrical equipment of the present invention can be conventional electrical equipment in the field, such as power equipment (such as electric vehicles), electronic equipment (such as computers, mobile phones, digital cameras, printers, fax machines, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), household appliances (such as air conditioners, refrigerators, washing machines, microwave ovens, etc.), etc., without special restrictions.
[0077] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0078] Example 1
[0079] The method for preparing the battery of this embodiment comprises the following steps:
[0080] 2g of conductive carbon black (specific surface area 70m 2 / g, oil absorption value is 270ml / 100g) is placed in a stainless steel mesh mold and then placed in an atomic layer deposition chamber as a whole, evacuated, the temperature of the chamber is maintained at about 250°C, trimethylaluminum vapor at room temperature is introduced into the chamber for 0.02s, then the chamber is evacuated and left to stand for 6s, water vapor at room temperature is introduced into the chamber for 0.02s, then the chamber is evacuated, and trimethylaluminum vapor is introduced again for 8s to complete a cycle of deposition. According to this step, the deposition is repeated 10 times to obtain Al2O3-coated carbon black material, i.e., conductive material.
[0081] The negative electrode active material artificial graphite, conductive material, thickener (CMC), and binder (SBR) are mixed in a ratio of 96:1:1:2, and the powder and deionized water are stirred into a negative electrode slurry using a homogenizer and evenly coated on the copper foil.
[0082] The positive electrode active material lithium iron phosphate (LiFePO4), conductive agent (CNT), and binder (PVDF) were mixed in a ratio of 97:1:2, and the powder and NMP were stirred into positive electrode slurry using a homogenizer and evenly coated on aluminum foil.
[0083] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1 to prepare an electrolyte containing 1M LiPF6.
[0084] A polypropylene separator was used to prepare a 1.7Ah stacked battery, and its rate charge and discharge performance and cycle performance were tested.
[0085] Example 2
[0086] The preparation methods of the battery of Example 2 are basically the same as those of Example 1, except that the aluminum source trimethylaluminum is replaced by the titanium source titanium tetrachloride, and the coating layer of the conductive material is titanium oxide.
[0087] Example 3
[0088] The preparation method of the battery of Example 3 is basically the same as that of Example 1, except that the number of cyclic deposition is changed to 5 times and the thickness of the aluminum oxide coating layer is adjusted to 2 nm.
[0089] Example 4
[0090] The preparation method of the battery of Example 4 is basically the same as that of Example 1, except that the number of cyclic deposition is changed to 30 times and the thickness of the aluminum oxide coating layer is adjusted to 20 nm.
[0091] Example 5
[0092] The preparation method of the battery in Example 5 is basically the same as that in Example 1, except that the specific surface area of the conductive carbon black is changed to 26 m2 / g, the specific surface area of the conductive material is 20m 2 / g.
[0093] Example 6
[0094] The preparation method of the battery in Example 6 is basically the same as that in Example 1, except that the specific surface area of the conductive carbon black is changed to 238 m 2 / g, the specific surface area of the conductive material is 200m 2 / g.
[0095] Example 7
[0096] The preparation method of the battery of Example 7 is basically the same as that of Example 1, except that the oil absorption value of the conductive carbon black is changed to 82 ml / 100 g, and the oil absorption value of the conductive material is obtained to be 100 ml / 100 g.
[0097] Example 8
[0098] The preparation method of the battery of Example 8 is basically the same as that of Example 1, except that the oil absorption value of the conductive carbon black is changed to 328 ml / 100 g, and the oil absorption value of the conductive material is obtained to be 350 ml / 100 g.
[0099] Example 9
[0100] The preparation method of the battery of Example 9 is basically the same as that of Example 1, except that the negative electrode active material artificial graphite, conductive material, thickener (CMC), and binder (SBR) are mixed in a ratio of 96.99:0.01:1:2, and the powder and deionized water are stirred into a negative electrode slurry using a homogenizer and evenly coated on the copper foil.
[0101] Example 10
[0102] The preparation method of the battery of Example 10 is basically the same as that of Example 1, except that the negative electrode active material artificial graphite, conductive material, thickener (CMC), and binder (SBR) are mixed in a ratio of 95:2:1:2, and the powder and deionized water are stirred into a negative electrode slurry using a homogenizer and evenly coated on the copper foil.
[0103] Embodiment 11
[0104] The preparation method of the battery in Example 11 is basically the same as that in Example 1, except that the conductive agent is replaced by carbon nanotubes (with a specific surface area of 75 m 2 / g, oil absorption value is 310ml / 100g).
[0105] Comparative Example 1
[0106] The preparation methods of the batteries of Comparative Example 1 and Example 9 are basically the same, except that the conductive material used does not have an inorganic oxide shell layer.
[0107] Comparative Example 2
[0108] The preparation method of the battery of Comparative Example 2 is basically the same as that of Example 1, except that the oil absorption value of the carbon black is changed to 63 ml / 100 g, and the oil absorption value of the conductive material is obtained to be 72 ml / 100 g.
[0109] Comparative Example 3
[0110] The preparation method of the battery of Comparative Example 3 is basically the same as that of Example 1, except that the oil absorption value of the carbon black is changed to 375 ml / 100 g, and the oil absorption value of the conductive material is obtained to be 390 ml / 100 g.
[0111] Test example:
[0112] Testing and extraction of conductive materials in negative electrode sheets: ① Take part of the negative electrode sheet (non-thinned area) and take a picture in an electron microscope and perform EDS characterization to observe whether it contains inorganic oxide materials and their dispersion state in the electrode sheet; ② Place the negative electrode sheet in a certain concentration of HCl solution, and accelerate the dissolution process by stirring or ultrasonic treatment to remove the Cu foil in the electrode sheet, SBR, CMC in the negative electrode active material layer, and SEI film in the carbon material, and then filter or centrifuge the solution and insoluble components. Dry the insoluble components and grind them into fine particles of a certain size, then mix them with an appropriate amount of solvent or dispersant, place them in an ultrasonic bath or use an ultrasonic probe for ultrasonic treatment to form a uniform suspension. During the ultrasonic treatment, due to the different properties of graphite and conductive materials, tiny aggregation and dispersion phenomena will occur. After the ultrasound is over, the sample is centrifuged and the centrifugal rate is adjusted to separate the graphite from the conductive material. The conductive material is dried, ground and powdered, and the corresponding characterization test is performed on it.
[0113] 1. Shell thickness: A transmission electron microscope (TEM) is used to test the shell thickness of conductive materials. The conductive material is first dispersed in an anhydrous ethanol solution to obtain a dispersion. The dispersion is then dropped onto a copper mesh for drying and sampling. The electron beam generated by an electron gun in a high vacuum environment penetrates the sample and focuses on the image. The thickness of the inorganic oxide shell is measured by observing the image on the display screen using the built-in calibration tool. The average value is calculated after measuring multiple areas to obtain the shell thickness.
[0114] 2. Specific surface area: The specific surface area of the conductive material is tested using the BET static method. The conductive material is first placed in a special adsorption instrument sample tube and subjected to high temperature pretreatment (nitrogen blowing and baking at 200°C for 2 hours) to remove surface impurities and moisture. Subsequently, an inert gas (usually nitrogen or other adsorbents) is brought into contact with the conductive material at a series of known relative pressures to achieve adsorption equilibrium. The instrument measures the amount of adsorption at different relative pressures, and based on these data and the BET theory, calculates the specific surface area.
[0115] 3. Oil absorption value: Use oil absorption value test equipment to test the oil absorption value of conductive materials. Take 10g of conductive material in the mixing bin, input the mass, click the start button, wait for the equipment test to complete, stop running and read the test value of the equipment. Repeat the test three times and calculate the average value, which is the oil absorption value of the conductive material.
[0116] 4. Liquid retention capacity: The negative electrode sheets prepared in the examples and comparative examples were baked at 120°C for 12 hours, and the mass of the negative electrode sheets after baking was recorded. Under a 25°C environment, the baked negative electrode sheets were immersed in the electrolyte for 48 hours and then taken out, and the mass of the negative electrode sheets after being immersed in the electrolyte was recorded to calculate the liquid retention capacity of the negative electrode sheets. The calculation formula for the liquid retention capacity is: liquid retention capacity = (mass of the negative electrode sheet after being immersed in the electrolyte - mass of the negative electrode sheet after baking) / mass of the coating of the negative electrode sheet.
[0117] 5. DC internal resistance: Charge and discharge the battery at 25°C and 0.2C to calibrate the battery capacity, then charge it at 0.2C to 50% SOC, then charge the battery at -10°C and charge it at 1 / 3C for 30s, record the termination voltage and termination current of each process, and calculate the DC internal resistance using the formula DCIR = (V1–V2) / (I2–I1), where V1 and I1 are the voltage and current before charging, and V2 and I2 are the voltage and current after charging.
[0118] 6. First coulombic efficiency: At 25°C, charge the battery at 0.1C constant current and constant voltage to 100% SOC, age it at 45°C for 24h, discharge it at 0.1C constant current to 0% SOC, record the charging capacity and discharging capacity, and calculate the first coulombic efficiency. First coulombic efficiency = discharge capacity / charge capacity*100%.
[0119] 7. Cycle performance: Charge the battery at 1C to a voltage of 3.8V at 45°C, leave it for 10 min, then discharge it at a discharge rate of 1C to a voltage of 2.0V, cycle it 500 times, and record the capacity retention rate; capacity retention rate after 500 cycles (%) = discharge specific capacity after 500 cycles / discharge specific capacity after the third cycle*100%.
[0120] Table 1
[0121]
[0122] As can be seen from Table 1, compared with the comparative example, the conductive material provided by the present invention includes a conductive agent and a shell layer present on the surface of the conductive agent, and the shell layer is an inorganic oxide, and the oil absorption value of the conductive material is 100mL / 100g-350mL / 100g. The conductive material is applied to the negative electrode sheet of the battery to improve the liquid absorption and retention capacity of the battery, reduce the low-temperature DC internal resistance of the battery, and take into account the improvement of the first coulomb efficiency and cycle life of the battery.
[0123] From the comparison between Example 1 and Comparative Examples 1-3, it can be seen that the conductive material provided by the present invention is applied to the negative electrode sheet of the battery, which can improve the battery's liquid absorption and retention capacity, reduce the battery's low-temperature DC internal resistance, and improve the battery's initial coulombic efficiency and cycle life.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive material, characterized in that: It includes a conductive agent and a shell layer present on the surface of the conductive agent, wherein the shell layer includes an inorganic oxide; The oil absorption value of the conductive material is 100 mL / 100 g to 350 mL / 100 g.
2. The conductive material according to claim 1, characterized in that The oil absorption value of the conductive material is 260 mL / 100 g to 350 mL / 100 g.
3. The conductive material according to claim 1 or 2, characterized in that: The specific surface area of the conductive material is 20 m 2 / g-200m 2 / g, preferably 50m 2 / g-80m 2 / g.
4. The conductive material according to any one of claims 1 to 3, characterized in that: The thickness of the shell layer is 2nm-20nm, preferably 3nm-6nm.
5. The conductive material according to any one of claims 1 to 4, characterized in that: The inorganic oxide includes at least one of aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, manganese oxide, and zinc oxide; And / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene.
6. A negative electrode sheet, characterized in that: The invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises the conductive material according to any one of claims 1 to 5.
7. The negative electrode sheet according to claim 6, characterized in that: The mass percentage of the conductive material in the negative electrode active material layer is 0.01%-2%; And / or, the negative electrode active material layer also includes a negative electrode active material, a thickener, and a binder, the mass percentage of the negative electrode active material in the negative electrode active material layer is 80%-98%, the mass percentage of the thickener in the negative electrode active material layer is 0.5%-5%, and the mass percentage of the binder in the negative electrode active material layer is 0.5%-5%.
8. A battery, characterized in that: Includes the negative electrode sheet as described in claim 6 or 7.
9. A battery pack, characterized in that: Comprising the battery as claimed in claim 8.
10. An electrical device, characterized in that: Comprising the battery according to claim 8 or the battery pack according to claim 9.
Citation Information
Patent Citations
Lithium ion cell anode material lithium vanadium phosphate and preparation method thereof
CN101145611A
Method for improving performance of conductive agent material of energy storage battery
CN105680052A
Non-aqueous electrolyte secondary battery
CN105745774A
Electrode pole plate and secondary battery
CN110828826A
Negative pole piece and secondary battery comprising same
CN114361457A